2007
DOI: 10.1152/ajplung.00391.2006
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of hypoxia-mediated decrease inIK(V)and increase in [Ca2+]cytin pulmonary artery smooth muscle cells

Abstract: Hypoxic pulmonary vasoconstriction is caused by a rise in cytosolic Ca(2+) ([Ca(2+)](cyt)) in pulmonary artery smooth muscle cells (PASMC) via multiple mechanisms. PASMC consist of heterogeneous phenotypes defined by contractility, proliferation, and apoptosis as well as by differences in expression and function of various genes. In rat PASMC, hypoxia-mediated decrease in voltage-gated K(+) (Kv) currents (I(K(V))) and increase in [Ca(2+)](cyt) were not uniformly distributed in all PASMC tested. Acute hypoxia d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 93 publications
(168 reference statements)
2
32
0
Order By: Relevance
“…It is noteworthy that these calcium signal time courses are similar to those we reported in rat pulmonary arteries [5]. In freshly dissociated or cultured smooth muscle cells from the same segment of rat pulmonary arteries, different smooth muscle cell phenotypes have been shown to correlate with the activity of different potassium channels [22] or different profiles of Ca 2+ responses to hypoxia or ATP, which mobilises intracellular calcium via G protein receptor activation [23]. The various patterns of calcium responses to 5-HT observed in the present study may, therefore, be related to different PASMC phenotypes which might relate to their physiological status.…”
Section: Effect Of 5-ht On Casupporting
confidence: 80%
“…It is noteworthy that these calcium signal time courses are similar to those we reported in rat pulmonary arteries [5]. In freshly dissociated or cultured smooth muscle cells from the same segment of rat pulmonary arteries, different smooth muscle cell phenotypes have been shown to correlate with the activity of different potassium channels [22] or different profiles of Ca 2+ responses to hypoxia or ATP, which mobilises intracellular calcium via G protein receptor activation [23]. The various patterns of calcium responses to 5-HT observed in the present study may, therefore, be related to different PASMC phenotypes which might relate to their physiological status.…”
Section: Effect Of 5-ht On Casupporting
confidence: 80%
“…In PASMCs, hypoxia-induced membrane depolarization has been attributed to the inhibition of oxygen-sensitive, voltagegated K + (K v ) channels, of which K v 1.5 and K v 2.1 are considered particularly relevant (20)(21)(22). To test the potential involvement of these channels in the hypoxic response of lung microvascular endothelial cells, we determined their expression and functionality in the intact mouse lung preparation.…”
Section: Cx40 Deficiency Attenuates Chronic Hypoxic Pulmonary Hypertementioning
confidence: 99%
“…24,25) However, it remains unclear whether these changes in Kv function and expression are etiologically linked to HA-PAH. The reduction of Kv channel activity and the subsequent membrane depolarization appear to be involved in the development of chronic pulmonary hypertension by mediating pulmonary vasoconstriction and vascular remodeling through an increase of [Ca 2+ ]i, 3,4,26) which suggests that PA remodeling is correlated with [Ca 2+ ]i. We showed that the [Ca 2+ ]i increased in the PAs of HA rats, which may be the mechanism underlying the specific Kv channel that mediates HA-PAH.…”
Section: Discussionmentioning
confidence: 61%
“…3,4,33) Our study indicates that DCA could inhibit the proliferation of PASMCs by up-regulating Kv channels and reducing ([Ca 2+ ]i). DCA enhances apoptosis in monocrotaline-induced PAH by increasing H 2 O 2 production.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation